Pengaruh Efektifitas Metode Tutor Sebaya Untuk Peningkatkan Hasil Belajar Peserta Didik Kelas XI Mata Pelajaran Akidah Akhlak Di Madrasah Aliyah Hidayatul Mubtadi’in Sidoharjo Kecamatan Jati Agung Kabupaten Lampung Selatan - Antis Carnela; Mujiyatun Mujiyatun; Mustafida Mustafida (Departement of Mathematics Education, 2024)
Peer tutor method, students are more actively involved in the learning process. Students are not only passive listeners, but also actively participate in discussions and learning activities. Collaboration between students helps create an interactive learning atmosphere, where they can ask questions, discuss, and teach each other. This improves their understanding because active learning is proven to be more effective than one-way learning. This study aims to analyze: (1) The effectiveness of the peer tutor method to improve the learning outcomes of class XI students in the subject of aqidah and akhlak at the Hidayatul Mubtadiin Sidoharjo Islamic High School. (2) What are the obstacles faced and solutions in the effectiveness of the peer tutor method to improve the learning outcomes of class XI students in the subject of aqidah and akhlak at the Hidayatul Mubtadiin Sidoharjo Islamic High School. This study uses a comparative research method that functions to compare two or more than one variable, event, activity or program. This study is descriptive quantitative, by providing pre-tests and post-tests to students. The results of this study indicate that the results of the hypothesis test that have been carried out in the trial class and the control class, the Sig. (ρvalue) = 0.000 <α = 0.05 is obtained. which means H0 is rejected H1 is accepted. Based on the results of these calculations, it can be concluded that there is an influence of the use of the peer tutor method on the learning outcomes of students in the subject of Akidah Akhlak class XI Madrasah Aliyah Hidayatul Mubtadi'in Jatiagung Lampung Selatan.